"Abaixo de Deus existe o CRAS!": avaliação em profundidade do serviço de proteção e atendimento integral à família no Centro de Referência de Assistência Social Jacarecanga em Fortaleza- Ceará - Oliveira, Leiliane Martinz de (2024)
This dissertation is about the in-depth evaluation of the main service of the Social Assistance Policy, within the scope of Basic Social Protection, the Family Protection and Comprehensive Care Service. The main objective of the study is to evaluate the experience of social work with families monitored at the Jacarecanga Social Assistance Reference Center, located in Fortaleza-Ceará, taking into account the four axes of in-depth evaluation: content analysis, context analysis, institutional trajectory and territorial and temporal spectrum. The evaluative focus is on the apprehension of the perceptions and meanings of the Social Assistance Policy, Family and Social Work with Families, listed by the families and SUAS professionals of the aforementioned facility. The interlocutors of the research were the narratives of the families who have been accompanied for at least five years and the professionals who run the PAIF, who have the same period of experience, with a view to understanding the conceptions and meanings of social work with families inscribed in their regulations within the scope of the Social Assistance Policy. Historically, the family has been central to Brazilian public policies and in the Social Assistance Policy the concept of the family is defined as a group of people who are united by ties of blood, affection and/or solidarity. In order to carry out this in-depth evaluative research, based on Rodrigues (2008), we opted for bibliographical, documentary and field research, with a qualitative methodological approach and quantitative and secondary data inputs. The data collection instruments were direct observation, with a field diary, and semi-structured interviews recorded and transcribed for the purposes of categorizing and interpreting the data and information. The central analytical categories were in-depth evaluation, social assistance policy, the family and social work with the family, as well as the cross-cutting categories/concepts of territory, poverty and social vulnerability. The theoretical analytical basis for the study in the categories listed is also supported by authors such as: Guba Lincoln and Lejano (2011), Gussi (2019), Behring and Boschetti (2011), Carvalho (2008), Couto, YazBek, and Raichelis, 2012, Castro and Bezerra (2015), Sarti (2017), Mioto (1997), Teixeira (2017), Koga (2003), Mota (2010), among others. The study revealed that all the users interviewed were women. It's worth noting that women seem to continue to take on the interim role, most of the time as the sole guardians of the family. With regard to race, the majority declared themselves to be brown, with one black user. In terms of schooling, the majority were literate, but most had not completed elementary school. As for the professionals interviewed, their statements identified two distinct perspectives in relation to understanding the Social Assistance Policy, a dispute between two opposing projects: the traditional model of assistance focused on immediate and historical care, and a critical approach that promotes social assistance as a public policy based on rights. Finally, the research reflects on the process of constitution of the Social Assistance Policy, highlighting the contradictions of social work with families within the scope of the PAIF, which are inherent to its effectiveness as a public social protection policy.